Volcanic forcing of the Lomagundi–Jatuli carbon isotope excursion - Janne Blichert-Toft; Kurt Konhauser; Baptiste Coutret; Marine Pinto; Arnaud Agranier; Abderrazzak El Albani; Francis Albarède (Proceedings of the National Academy of Sciences, 2025)
The Lomagundi–Jatuli Event (LJE), Earth’s most pronounced and prolonged positive carbon isotope excursion, followed the Great Oxidation Event and remains enigmatic in origin. We present a Pb–Pb isochron age of 2,194 ± 5 Ma for black shales from the Francevillian FB Formation, Gabon—an LJE type locality—coinciding with the emplacement of the Large Igneous Province that gave rise to the extensive Birimian–Eburnean orogenic segment. This orogeny produced very large volumes of juvenile crust in the form of oceanic plateau basalts that were eventually reworked through subduction and collisions. These processes released substantial volcanic CO 2 into the ocean–atmosphere system, disrupting the carbon and oxygen cycles for 100 to 200 My. Volcanic outgassing likely outpaced alkalinity production from weathering, leading to an increase in the δ 13 C of sedimentary carbonates. Reanalysis of global δ 13 C–δ 18 O datasets reveals a previously unrecognized dual bimodality, attributed here to episodic volcanic degassing and subsequent oceanic carbonate saturation. Weathering of emergent crust enhanced nutrient fluxes, driving primary productivity and organic carbon burial. We further propose that volcanic CO 2 emissions modulated the Dole Effect by shifting the balance between terrestrial and marine photosynthetic oxygen production, altering atmospheric oxygen isotope ratios independently of climate. These processes collectively drove the δ 13 C excursion of the LJE and may have fostered conditions conducive for early eukaryotic evolution.